To simplify the expression \((3r \cdot 5) \cdot (-3 \cdot 8)\), we will break it down step by step.
-
Calculate \(3r \cdot 5\): \[ 3r \cdot 5 = 15r \]
-
Calculate \(-3 \cdot 8\): \[ -3 \cdot 8 = -24 \]
-
Now combine the results: \[ (3r \cdot 5) \cdot (-3 \cdot 8) = 15r \cdot (-24) \]
-
Break down the multiplication: \[ 15r \cdot (-24) = -360r \]
Now, let's consider the options provided:
- \((5 \cdot -3) \cdot -9r\): This does not match our result.
- \(15r \cdot (5 \cdot 8)\): This simplifies to \(15r \cdot 40 = 600r\), which does not match.
- \(-45r \cdot 5\): This simplifies to \(-225r\), which does not match.
- \(24r \cdot (5 \cdot -3)\): The expression inside the parentheses is \(5 \cdot -3 = -15\), leading to \(24r \cdot -15 = -360r\), which matches our result.
Thus, the equivalent expression is:
\[ \boxed{24r \cdot (5 \cdot -3)} \]